Efficacy of methylene blue for on vasoplegic syndrome - Mohsen akhondi; Alireza Sabzevari; Shabnam Imannezhad; Ali Rahdari (Reviews in Clinical Medicine, 2016)
Introduction: Administration of methylene blue has been proposed as a therapeutic strategy in the treatment of vasopelgic shock following cardiac surgery. Major aims of this systematic review were to evaluate the effect of methylene blue on mortality rate, duration of vasoplegic syndrome, and further complications of patients with vasoplegic syndrome following cardiac surgery. Methods: PubMed was searched to obtain the most relevant articles. All the randomized control trials and cohort studies were included.Result: A total of 54 articles were retrieved at the initial search. After studying the titles, abstracts, and full text of the articles, only five articles consisted of two randomized controlled trials (RCTs) and two observational studies were included.Discussion: Based on included RCTs, the mortality rate and duration of the disease decreased in patients applied methylene blue in the treatment of vasoplegic syndrome compared with those did not receive this medication.Conclusions: Bbased on included articles, application of methylene blue could be suggested as a treatment for vasoplegic syndrome, but further large multicenter RCTs are needed to certainly evaluate the efficacy of methylene blue.